Perbedaan Hardiness Pada Mahasiswa Universitas Muhammadiyah Surakarta Ditinjau Dari Keikutsertaan Organisasi - Taris Wicaksono, Eko, Susatyo Yuwono ,S. Psi, M. Si., Psi (2016)
This study aims to determine hardiness personality possessed by students who joined the organization and does not follow the organization Muhammadiyah University of Surakarta. This study was conducted in 12 faculties of the University of Muhammadiyah Surakarta, namely the Faculty of Education (Guidance and Counseling), Faculty of Economics and Business (FEB), Faculty of Law (FH), Faculty of Engineering (FT), Faculty of Geography, Faculty of Psychology, Faculty of Islamic Studies (FAI ), Faculty of Medicine (FK), Faculty of Dentistry (FKG), Faculty of Health Sciences (FIK), Faculty of Pharmacy, Faculty of Communication and Information (FKI) and has 153 student organizations. Research subjects in this research were 360 people with 180 students who follow the activities of student organizations and 180 students who do not follow the activities of student organizations. Sampling is done by proportional sampling technique. The method used in this penlitian is a quantitative method by using religious orientation scale. This research data analysis techniques using independent sample t-tests. Based on the results of independent testing of samples t-test t-test values obtained at t = 4.102 with a coefficient value sig (2-tailed) = 0,000 which means there is a resilient personality differences in students who joined the organization and does not follow the organization Muhammadiyah University of Surakarta. Keywords : hardiness, educational institutions